Urgensi Living Qur'an Dalam Kehidupan Masyarakat - Mario Mega Zaputra; Rosmini Amin; Muhsin Mahfudz; Luzy Nurhalifah (Jurnal Ilmu Agama Indonesia, 2026)
This article examines the urgency of the Living Qur'an in the lives of contemporary Muslim communities. The Living Qur'an is understood as a socio-religious phenomenon in which the Qur'an is not merely present as a written text but is actively lived, practiced, and functions across various aspects of community life. Employing a descriptive qualitative approach and library research, this study analyzes the significance of the Living Qur'an from three primary dimensions: spiritual, social, and cultural. The findings indicate that the Living Qur'an plays a fundamental and irreplaceable role in Muslim society. Spiritually, it serves as a source of spiritual strength and psychological well-being. Socially, it functions as a unifying force that strengthens social cohesion and facilitates the intergenerational transmission of moral values. Culturally, the Living Qur'an represents both a marker of cultural identity and a safeguard for religious and ethical values amid the challenges of globalization. In the contemporary era, the Living Qur'an faces challenges posed by modernization and secularization while simultaneously embracing new opportunities through digital media. This article concludes that the integrative and multidisciplinary revitalization of the Living Qur'an is essential for fostering a Muslim society that is characterized by strong moral values, civility, and competitiveness.